2021
DOI: 10.1039/d1tb01848e
|View full text |Cite
|
Sign up to set email alerts
|

Various administration forms of decellularized amniotic membrane extract towards improving corneal repair

Abstract: Amniotic membrane (AM) transplantation is often used as a treatment for corneal repair, but the AM is prone to dissolving and shedding after surgery; multiple transplants will cause pain and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It also influences fibroblast and myofibroblast differentiation by modulating collagen production and induces angiogenesis by promoting endothelial cell migration [ 115 ]. Particularly, a decellularized ECM from the amniotic membrane exhibited increased wound healing efficiency in severe corneal injury, being characterized with a shorter healing time for CEpi and a faster recovery for stromal opacity and thickness, compared with the control eyes [ 116 ].…”
Section: Cell-free Approach For Stromal Wound Healing and Regenerationmentioning
confidence: 99%
“…It also influences fibroblast and myofibroblast differentiation by modulating collagen production and induces angiogenesis by promoting endothelial cell migration [ 115 ]. Particularly, a decellularized ECM from the amniotic membrane exhibited increased wound healing efficiency in severe corneal injury, being characterized with a shorter healing time for CEpi and a faster recovery for stromal opacity and thickness, compared with the control eyes [ 116 ].…”
Section: Cell-free Approach For Stromal Wound Healing and Regenerationmentioning
confidence: 99%
“…Nevertheless, the incorporation of AM extract into various hydrogel formulations for treating ocular diseases has been exploited in several cases. For example, Luo et al (2021) proposed the application of dAM extract (dAME) in different ways, such as eye drops, and the incorporation of dAME in temperature-sensitive P407 hydrogels or freeze-dried PVA tablets to treat corneas with acid burns. Treatment of severe corneal burns with these three alternatives was accompanied by the best results in terms of less stromal opacity and faster corneal regeneration for in situ forming dAME containing P407 hydrogel, followed by second best results for dAME containing PVA tablets, and moderate results for dAME liquid drop.…”
Section: Biomedical Applications Of Am-derived Hydrogelsmentioning
confidence: 99%
“…Our group administered severe corneal injury by AME-derived composites in the form of in situ gels or tablets. The results showed that AME could promote wound healing, with the in situ gels having the most significant therapeutic efficiency [ 152 ].…”
Section: Applications Of Ham and Its Composites In Tissue Engineeringmentioning
confidence: 99%